A Comparative Analysis of Traditional Methods and Communicative Language Teaching in Relation to Students’ Academic and Communicative Achievement - Yede, Francis Setonji (European Scientific Journal, ESJ, 2020)
This research is a comparative analysis of Traditional Methods and Communicative Language Teaching (CLT) and their ability to facilitate students’ academic and communicative achievement at Basic Education level. Students and teachers of English as a Second Language (ESL) from secondary schools within the Badagry Local Educational District of Lagos State, Nigeria, were randomly selected and sampled as the population of the study. Remedial treatment was given to the experimental group and later, proficiency test was given to both the experimental and the control groups to measure the ability to carry out specific communicative tasks in ESL. The observation checklist and the diagnostic test (pretest) were analysed using descriptive and inferential statistics of mean, standard deviation and t-test. Data analysis revealed that the traditional method being utilised in teaching English language in L2 situations cannot promote adequate communicative competence expected of the learners of ESL at the secondary School level. The linguistic performances of the control group students in the post-tests were low and, this calls for adoption of a functional language teaching model to promote adequate communicative skills in the learners. The performance of the experimental group revealed that CLT promotes free language use and interpersonal communication skills in ESL and thereby enhances communicative competence in the learners. Teachers of ESL need to be equipped with the skills of CLT in order to achieve the goals of linguistic competence in their teaching.